Rapid Shifts in Bacterial Communities and Homogeneity of Symbiodiniaceae in Colonies of Pocillopora acuta Transplanted Between Reef and Mangrove Environments - Haydon, Trent D.; Seymour, Justin R.; Raina, Jean-Baptiste; Edmondson, John; Siboni, Nachshon; Matthews, Jennifer L.; Camp, Emma F.; Suggett, David J. (Frontiers in Microbiology, 2021)
It has been proposed that an effective approach for predicting whether and how reef-forming corals persist under future climate change is to examine populations thriving in present day extreme environments, such as mangrove lagoons, where water temperatures can exceed those of reef environments by more than 3°C, pH levels are more acidic (pH <7.9, often below 7.6) and O2 is regularly considered hypoxic (<2 mg/L). Defining the physiological features of these “extreme” corals, as well as their relationships with the, often symbiotic, organisms within their microbiome, could increase our understanding of how corals will persist into the future. To better understand coral-microbe relationships that potentially underpin coral persistence within extreme mangrove environments, we therefore conducted a nine-month reciprocal transplant experiment, whereby specimens of the coral Pocillopora acuta were transplanted between adjacent mangrove and reef sites on the northern Great Barrier Reef. Bacterial communities associated with P. acuta specimens native to the reef environment were dominated by Endozoicomonas, while Symbiodiniaceae communities were dominated by members of the Cladocopium genus. In contrast, P. acuta colonies native to the mangrove site exhibited highly diverse bacterial communities with no dominating members, and Symbiodiniaceae communities dominated by Durusdinium. All corals survived for 9 months after being transplanted from reef-to-mangrove, mangrove-to-reef environments (as well as control within environment transplants), and during this time there were significant changes in the bacterial communities, but not in the Symbiodiniaceae communities or their photo-physiological functioning. In reef-to-mangrove transplanted corals, there were varied, but sometimes rapid shifts in the associated bacterial communities, including a loss of “core” bacterial members after 9 months where coral bacterial communities began to resemble those of the native mangrove corals. Bacterial communities associated with mangrove-to-reef P. acuta colonies also changed from their original composition, but remained different to the native reef corals. Our data demonstrates that P. acuta associated bacterial communities are strongly influenced by changes in environmental conditions, whereas Symbiodiniaceae associated communities remain highly stable.